Comparing the Effect of Activated Charcoal Whitening Agents against Regular Whitening Toothpastes on the Enamel Surface of Premolar Teeth: In vitro Study - Mourad, Lougine Mostafa El-Khousht Mahmoud; Elzainy, Medhat Ahmed; Hussein , Safaa Ismail (Open Access Macedonian Journal of Medical Sciences, 2022)
INTRODUCTION: There has been increase in demand to use natural whitening agents nowadays which include activated charcoal. Activated charcoal has gained popularity recently with various claims to its benefits that have not been proven. AIM: The aim of the study was to evaluate the effect of activated charcoal whitening agents and regular whitening tooth paste on enamel surface of first premolars and to compare between the effects of materials used. MATERIALS AND METHODS: Twenty-one mandibular first premolars were used and divided into control group: untreated teeth that were later incorporated into experimental group. Experimental group: Consisting of three subgroups: Subgroup I: treated with Carbon Coco. Subgroup II: treated with Venu activated charcoal. Subgroup III: treated with Crest 3D white. Brushing was done nine s for 30 days then teeth were preserved in artificial saliva. RESULTS: Scanning electron microscopic results showed areas with rodless enamel more observed in Subgroup III than Subgroups I and II. EREs were more numerous on Subgroups I and II than Subgroup III on enamel surface. Partially occluded EREs with precipitates were more observed on Subgroups I and II than Subgroup III. Energy dispersive X-ray analysis results for calcium showed significant increase between all groups with control. The highest value was recorded in Subgroup II followed by Subgroups I and III while control group was the lowest one. Phosphorous showed significant increase between all groups with control. The highest value was recorded in Subgroup I followed by Subgroups III and II while control group was the lowest one. Micro-hardness results of Subgroups I and II showed significant increase compared to control group and no significant difference between control and Subgroup III was detected. CONCLUSION: Powder form activated charcoal is more abrasive than whitening toothpastes. There is no visible difference between pure 100% activated charcoal powder and charcoal powder with additives to it.v